Total liver phosphatidylcholine content associates with non‐alcoholic steatohepatitis and glycine N‐methyltransferase expression - Männistö, Ville; Kaminska, Dorota; Kärjä, Vesa; Tiainen, Mika; de Mello, Vanessa D.; Hanhineva, Kati; Soininen, Pasi; Ala‐Korpela, Mika; Pihlajamäki, Jussi (Liver international, 2019)
Background & Aims Alterations in liver phosphatidylcholine (PC) metabolism have been implicated in the pathogenesis of non‐alcoholic fatty liver disease (NAFLD). Although genetic variation in the phosphatidylethanolamine N‐methyltransferase (PEMT) enzyme synthesizing PC has been associated with disease, the functional mechanism linking PC metabolism to the pathogenesis of non‐alcoholic steatohepatitis (NASH) remains unclear. Methods Serum PC levels and liver PC contents were measured using proton nuclear magnetic resonance (NMR) spectroscopy in 169 obese individuals [age 46.6 ± 10 (mean ± SD) years, BMI 43.3 ± 6 kg/m2, 53 men and 116 women] with histological assessment of NAFLD; 106 of these had a distinct liver phenotype. All subjects were genotyped for PEMT rs7946 and liver mRNA expression of PEMT and glycine N‐methyltransferase (GNMT) was analysed. Results Liver PC content was lower in those with NASH (P = 1.8 x 10−6) while serum PC levels did not differ between individuals with NASH and normal liver (P = 0.591). Interestingly, serum and liver PC did not correlate (rs = −0.047, P = 0.557). Serum PC and serum cholesterol levels correlated strongly (rs = 0.866, P = 7.1 x 10−49), while liver PC content did not correlate with serum cholesterol (rs = 0.065, P = 0.413). Neither PEMT V175M genotype nor PEMT expression explained the association between liver PC content and NASH. Instead, liver GNMT mRNA expression was decreased in those with NASH (P = 3.8 x 10−4) and correlated with liver PC content (rs = 0.265, P = 0.001). Conclusions Decreased liver PC content in individuals with the NASH is independent of PEMT V175M genotype and could be partly linked to decreased GNMT expression.